Craniopharyngioma presenting with severe hyponatremia, hyponatremia-induced myopathy, and panhypopituitarism: a case report. (December 2017) - Dilrukshi, M.; Sandakumari, G.; Abeysundara, P.; Chang, T.
Abstract Background Craniopharyngiomas are rare intracranial tumors commonly presenting with neurological symptoms. Reports of severe hyponatremia as a presenting manifestation of a craniopharyngioma and hyponatremia-induced myopathy are rare. We report the case of a patient with craniopharyngioma presenting with severe hyponatremia, panhypopituitarism, and hyponatremia-induced myopathy. Case presentation A 52-year-old Sri Lankan man presented with anorexia, nausea, fatigue, generalized muscle weakness, and cramps for 1 week. The onset of his illness had been preceded by vomiting and diarrhea for 1 day which he attributed to food poisoning. On examination, he had an apathetic disposition with a generalized "sallow complexion." He was not dehydrated. Apart from reduced muscle power (4/5) and hyporeflexia, the neurological examination was normal. His serum sodium was 102 mmol/l; potassium 4.1 mmol/l; chloride 63 mmol/l; plasma osmolality 272 mosm/KgH2 O; urine osmolality 642 mosm/KgH2 O; and urine sodium 79 mmol/l. His creatine phosphokinase was 12, 400 U/l, lactate dehydrogenase 628 U/l, aspartate aminotransferase 360 U/l, and alanine aminotransferase 64 U/l. His hormone profile revealed panhypopituitarism. An electromyogram showed nonspecific abnormalities while a muscle biopsy did not show any pathology. Magnetic resonance imaging of his brain demonstrated a well-defined craniopharyngioma with suprasellar extension. His pituitary gland was compressed and the pituitary stalk was displaced by the tumor. He had marked improvement in muscle power and rapid reduction of serum creatine phosphokinase levels paralleling the correction of severe hyponatremia, even before the initiation of hormone replacement. Conclusions This case illustrates the rare presentation of severe hyponatremia and hyponatremia-induced myopathy in patients with craniopharyngioma, awareness of which would facilitate early appropriate investigations and treatment.